‘I Am Poor and Needy’: The Worshipper’s Posture Within the Psalter’s Structure - Dunham Kyle C. (Perichoresis: The Theological Journal of Emanuel University)
This study builds upon Johannes Bremer’s thesis that the main theme of the Psalter is YHWH’s concern for the poor (the so-called Armentheologie or theology of the poor). I argue that the phrase ‘poor and needy’ does not occur randomly through the Psalter but at strategic junctures. Traced from its inception to conclusion, seven Psalms (35, 37, 40, 70, 74, 86, 109) utilize this phrase to create a trajectory that moves from suffering to triumph, from oppression to deliverance, from denigration to vindication. Along this plotline, the psalmist identifies himself with the poor and needy in a way that grounds a messianic horizon for the Psalter, foreshadowing its consummation in Jesus Christ, the ultimate royal sage who promises ‘blessing’ (ashre) for the ‘poor in spirit’ who inherit the heavenly kingdom alongside the Psalter’s poor petitioner (Psalm 72:8-14; Matthew 3:2; Luke 6:20). The Psalter thus provides hope in the midst of suffering, as the poor and needy praise God’s name after deliverance and thank him for his abundant steadfast love, culminating in God’s ultimate victory through their (eschatological) deliverance.